Thermophysical Properties of Cryoprotectants. I. Temperature and Heat of Melting - Todrin, A. F.; Popivnenko, L. I.; Kovalenko, S. Ye. (Problems of Cryobiology and Cryomedicine, 2009)
The data from different literature sources about temperature and heat of melting for aqueous solutions of some cryoprotectants were systematised. There were obtained the empirical formulae to calculate melting temperatures for aqueous solution of 38 cryoprotectants depending on their mass concentration, as well as the ones to calculate the latent heat of melting for aqueous solutions of 11 cryoprotectants versus their mass concentration and for 3 cryoprotectants and water depending on overcooling.